Development of highly reinforced acrylonitrile butadiene rubber composites via controlled loading of sol-gel titania. (27th January 2017) - Das, Chayan; Bansod, Naresh D.; Kapgate, Bharat P.; Reuter, Uta; Heinrich, Gert; Das, Amit
Abstract: Remarkable improvement in mechanical properties of acrylonitrile butadiene rubber (NBR) composites is achieved by incorporating nano-titania that is synthesised in solution of the raw rubber using titanium n -butoxide (TNB) as the titania precursor. This is achieved by designed and controlled incorporation of titania that resulted in very good dispersion of titania of nanometric dimension in rubber matrix and enhanced rubber-filler interaction. This sol-gel transformation is carried out under optimised reaction condition. Surface modification of titania by a silane coupling agent (bis-(3-triethoxysilylpropyl)-tetrasulfide, TESPT) causes further improvement in filler dispersion and composite properties when added in the reactive sol-gel system during in situ titania generation rather than it's external addition in the titania filled NBR during mixing and compounding. Thorough characterisation of the composites are done that encompasses a wide range of studies on thermal, morphological, mechanical, dielectric, dynamic mechanical, rheological and antifungal properties. The results are analysed on a comparative basis to investigate the effect of in situ  incorporation and in situ surface modification of titania on the composite properties. Graphical abstract: Highlights: Uniformly distributed nanometric titania is grown in situ in NBR by solution sol-gel method in a controlled manner. Superior reinforcing character of sol-gel derived in situ titania is exhibited for NBR composites. Mechanical properties of the in situ filled composites become significantly higher than the externally filled composite. Enhanced rubber-filler interaction is established by DMA analysis. Dielectric study indicates that development of crystallinity for the in situ titania can deliver rich dielectric properties.